1992
DOI: 10.1093/infdis/166.1.113
|View full text |Cite
|
Sign up to set email alerts
|

Belgrade Virus: A New Hantavirus Causing Severe Hemorrhagic Fever with Renal Syndrome in Yugoslavia

Abstract: Two biologically and genetically distinct hantaviruses were isolated from blood and urine specimens collected from four Yugoslavian patients with clinically severe hemorrhagic fever with renal syndrome (HFRS). Viral isolates from three patients, designated strains Belgrade 1-3, were distinct from Hantaan, Seoul, Puumala, and Prospect Hill viruses as determined by plaque-reduction neutralization tests and restriction analysis of enzymatically amplified M-segment fragments. The fourth isolate, called Kraljevo, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(23 citation statements)
references
References 16 publications
0
23
0
Order By: Relevance
“…However, during the period from 1991 to 2006, three large DOBVassociated HFRS outbreaks were registered in the central regions of European Russia (34). A detailed investigation of the 2001-2002 outbreak revealed that the striped field mouse (Apodemus agrarius) was the virus reservoir and that the A. agrarius-borne DOBV lineage (DOBV-Aa) was the causative infectious agent (15,33).Three DOBV genetic lineages, 11,15,33), 2,3,7,9,22,23),33), have so far been demonstrated by molecular methods to cause HFRS in humans. The Saaremaa virus can be considered a fourth DOBV genetic lineage (21); however, it has not been detected in HFRS patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, during the period from 1991 to 2006, three large DOBVassociated HFRS outbreaks were registered in the central regions of European Russia (34). A detailed investigation of the 2001-2002 outbreak revealed that the striped field mouse (Apodemus agrarius) was the virus reservoir and that the A. agrarius-borne DOBV lineage (DOBV-Aa) was the causative infectious agent (15,33).Three DOBV genetic lineages, 11,15,33), 2,3,7,9,22,23),33), have so far been demonstrated by molecular methods to cause HFRS in humans. The Saaremaa virus can be considered a fourth DOBV genetic lineage (21); however, it has not been detected in HFRS patients.…”
mentioning
confidence: 99%
“…Three DOBV genetic lineages, 11,15,33), 2,3,7,9,22,23),33), have so far been demonstrated by molecular methods to cause HFRS in humans. The Saaremaa virus can be considered a fourth DOBV genetic lineage (21); however, it has not been detected in HFRS patients.…”
mentioning
confidence: 99%
“…Infection is normally transmitted to man by inhalation of dried excreta (urine or faeces) of the reservoir host. Hantavirus is subdivided into at least 18 ( Belgrade [72]. In addition to.…”
Section: The Virusmentioning
confidence: 99%
“…In addition to. HFRS, Belgrade also appears to cause hantavirus pulmonary syndrome (HPS) [72]. Two 'new' Hantaan-like viruses have been isolated from the lungs of bats (Rhinolophus ferrum-equinum and Eptesicus serotinus) but their role in human disease is unknown [73].…”
Section: The Virusmentioning
confidence: 99%
See 1 more Smart Citation